Aplicação de uma sequencia didática no ensino de Biologia - Mota, João Gláucio Siqueira Matos (2017)
Over the last few decades, we can see the great challenges that have not yet been overcome in the field of Science Education, and more particularly in the sub-area of Teaching Biology, where biology teaching has seen in its contents and methodologies a directionality almost exclusively of preparation of the student for vestibular exams, to the detriment of the purposes assigned by the Law of Guidelines and Bases of National Education - Law 9394/96. In this sense, it is necessary to use innovative methodologies for teaching, in order to stimulate students to think and produce new knowledge, contextualizing and problematizing before their reality, we can mention the practice of accomplishment of a Didactic Sequence (SD). The purpose of this study was to evaluate the learning process on the Kingdom Fungi content, using as a tool the application of SD in a high school class of a public school in the municipality of Tauá-Ce . As for the theoretical-methodological basis of the research, we used the dynamics of the pedagogical moments organized by Delizoicov (1991, 2002, 2008) and Gehlen, Maldaner and Delizoicov (2012). And as a method of information collection, the application of a semi-structured questionnaire containing eight questions, which expresses the evaluation analysis of the biology discipline (pre-test) and its implications of use in its daily life, as well as a learning assessment of the students , after the experience of a DS. As results found, we evaluated how important it is to diversify the tools for teaching in order to achieve a better learning in a larger number of students. It is up to the educator to reflect on his practice in search of replanning his actions, overcoming his limitations in his pedagogical action. As an educational product, we proposed the construction of a booklet in the printed version, to facilitate its dissemination among our peers, and the use of a digital version, established on the flipsnack.com.br platform as a medium of wide diffusion. In view of the fact that the information technology used for teaching must come together to foster the exchange of experiences.